Production techniques in natural farming - Sangma, Christy B. K.; Biswakarma, Niraj; Nongtdu, Deimonlang; Makdoh, Badapmain; Hazarika, Samarendra; Mishra, V. K. (Indian Farming, 2025)
Natural farming (NF) is an ecological farming approach which relies on environment friendly agricultural inputs and practices for improving soil health, agro-biodiversity, and self-sustaining production system. NF, an indigenous cow-based farming is based on the five components, viz. Beejamrit, Jivamrit, Acchadana, Whapasa and plant protection measures using cow dung and urine as the main ingredient in all its bio-formulations. Considering the nationwide promotional activities on NF, various comparative experimental trials were conducted in ICAR Research Complex for NEH Region, Umiam on NF with organic farming and integrated crop management practices for acidic soils of hill region. Three different case studies on NF field trials on different crops are presented here addressing its impact on soil, crop yield, and profitability in the region.